Penerapan Genetic Algorithm Untuk Optimasi Peningkatan Laba Persediaan Produksi Pakaian - Bryan Pratama Jocom; Nurul Hidayat; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Clothes as one of human need, in which the demand of clothing from time to time may increase or decrease. With the uncertainty of market demand for clothing making clothing sales into a promising business if appropriate in meeting market needs. Distro is an individual business or a group engaged in the production, marketing, and sales of clothing especially for young people. The success of the distro is measured by the amount of profit from clothing sales. Production design is one such factor. The problem will become more complex when there are many types of clothing sold, many sizes, and little capital in a month. Genetic algorithm is a meta-heuristic method that can solve the problem of clothing production. Proper fitness formula formulation can provide a value of chromosomes in the genetic algorithm, so the genetic algorithm can work best to solve production planning problems. The correct genetic algorithm parameters can give maximum results. The test shows the best results at the iteration of 75, the number of chromosomes by 425, the crossover rate of 0.9, and the mutation rate of 0.1. This study provides that genetic algorithm can solve complexity problems of production planning.